The Role of Virtual Reality in Enhancing Experiential Learning: A Comparative Study of Traditional and Immersive Learning Environments - Ibnu Fitrianto; Ali Saif (International Journal of Post Axial: Futuristic Teaching and Learning, 2024)
This study explores the role of Virtual Reality (VR) in enhancing experiential learning, comparing traditional and immersive learning environments through a descriptive qualitative design. By integrating VR into educational settings, we aim to understand how this technology affects student engagement and comprehension. Data were collected through interviews, observations, and content analysis of VR-based and traditional classroom activities. The findings reveal that VR significantly increases student engagement and understanding by providing immersive, interactive, and hands-on learning experiences. Students demonstrated higher levels of participation, deeper understanding of complex concepts, and improved retention of knowledge in VR environments compared to traditional methods. The study also identifies technical and pedagogical challenges, including the need for robust infrastructure, teacher training, and curriculum alignment. Based on these insights, recommendations are made for curriculum design, teacher professional development, and equitable access to VR technology. Future research should focus on the long-term impacts of VR, its application across different subjects, and strategies for overcoming implementation barriers. This research underscores the transformative potential of VR in education, advocating for its thoughtful integration to enhance learning outcomes.